Tragacanth gum-based hydrogels for drug delivery and tissue engineering applications - Abdi, Gholamreza; Jain, Mukul; Patil, Nil; Tariq, Mohd.; Choudhary, Shipra; Kumar, Pankaj; Raj, Neeraja S.; Mohsen Ali, Saif Saleh; Uthappa, U. T. (Frontiers in Materials, 2024)
Tragacanth gum is one of the natural polymers, which has a wide variety of application. Due to their accessibility, affordability, structural variety, and exceptional qualities as 'green' bio-based renewable materials, natural gums have drawn a lot of attention. Due to their ability to either form Gel or the viscous solution, a group of naturally occurring polysaccharides are referred to as gum. One of the plentiful raw components derived from vegetation is these polysaccharide gums. Having the ability to mimic living tissues, hydrogels are three-dimensional polymeric webs with high water or biological exudate absorption capacities that have shown great promise as tunable biomaterials thus far in a variety of regenerative approaches. Natural polysaccharides, or gums, can be found in numerous tree genera and have remarkable qualities including being renewable, biocompatible, biodegradable, and This is a provisional file, not the final typeset article non-toxic, as well as being easily chemically modifiable. Aspects of the food, water, energy, biotechnology, environment, and medical industries have recently drawn a lot of interest. Food gum, a form of very significant and distinctive food additive, serves several crucial purposes in the food industry. Due to their excellent structural versatility and high water-affinity, they are also used in nonfood industries like cosmetics, coating, photosensitive resin, fertiliser, casting, tobacco, and pharmaceuticals. When compared to hydrogels with a synthetic origin, those based on natural gums offer a number of advantageous qualities. Due to their widespread use in pharmaceutical and medical fields, synthesis hydrogel polymers have garnered the most attention among these non-food applications. In this article, we have concentrated on the hydrogels made from Tragacanth gum that are employed for tissue engineering and drug delivery. Extraction of Tragacanth gum, drug delivery, physical-chemical properties, and various biomedical applications, such as bone tissue engineering, skin tissue engineering, bone tissue fixation, periodontal tissue engineering, and cartilage tissue engineering, were also the focus of our attention. We also concentrated on potential futures based on Tragacanth gum hydrogels.